2010
DOI: 10.1074/jbc.m109.097196
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Repositioning of Dorsal to Two Different κB Motifs Controls Its Autoregulation during Immune Response in Drosophila

Abstract: I for activation and (ii) Dl-AP1-B P for repression. These two subcircuits are temporally delineated and bring about overall regulation of dorsal during immune response. These results suggest the presence of a previously unknown mechanism of Dorsal autoregulation in immune-challenged Drosophila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…However, the major groove geometry of A 6– containing κB motifs (Figure 5B and C) is distinct from that of the T 6 motifs (Figure 5D–F). We found that these two motifs have constrained major grooves and form repressor type DNA-Dl complexes (Figure 5B, C and G, lanes 6 and 7) (39). …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the major groove geometry of A 6– containing κB motifs (Figure 5B and C) is distinct from that of the T 6 motifs (Figure 5D–F). We found that these two motifs have constrained major grooves and form repressor type DNA-Dl complexes (Figure 5B, C and G, lanes 6 and 7) (39). …”
Section: Resultsmentioning
confidence: 97%
“…While dlκB I is a typical κB -motif ( GGGAATTCC ) and acts as an enhancer, atypical dlκB P ( AGAAAAACA ) acts as a repressor (39). For the functional assay, these motifs were placed at the dlκB P position in the dorsal promoter construct with a luciferase reporter (39).
Figure 2.Enhancer or repressor activity of κB -motifs is encoded in its sequence.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in Drosophila have suggested that specificity in target recognition by Hox proteins is determined by minor groove shape while that of the Dorsal target genes is ascertained by the major groove geometry ( 3 , 28 , 29 ). This has brought focus on the shape readout of the DNA motif in determining specificity in its interaction with TFs ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting simultaneously several viral genes from a single transgene construct is possible since only a few hundredbasepair long double-strand RNA sequence is sufficient to elicit RNA interference in the silkworm (Gandhe et al 2007;Mrinal and Nagaraju 2010;Shukla and Nagaraju 2010;Terenius et al 2011). With the aim of installing a strong antiviral trait, we assayed the properties of a transgene carrying four tandem sequences arising from four essential genes of the baculovirus (ie1, lef1, lef3, and p74).…”
mentioning
confidence: 99%